2023
DOI: 10.3390/ijerph20053798
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Noise at Moderate Levels Affects Cognitive Performance: Do Distance-Induced Temporal Changes Matter?

Abstract: Urbanization leads to an increased demand for urban housing, which can be met by building dwellings closer to streets. Regulations often limit equivalent sound pressure levels which do not account for changes in time structure that occur when decreasing the road distance. This study investigates the effect of such temporal changes on subjective workload and cognitive performance. A group of 42 participants performed a continuous performance test as well as a NASA-TLX workload test under three different sound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Both found that decreases were found in performing both mental and manual activities as the sound levels increased. On the other hand, at noise levels as low as 40 dB, the negative connotation of external road traffic noise can be responsible for the decline in working performance ( Müller et al, 2023 ). This means that less frequent negative events (e.g., cars or motos pass-by and sirens) combined with natural or anthropic sounds may induce a positive emotional state in the individuals without draining attentive sources.…”
Section: Resultsmentioning
confidence: 99%
“…Both found that decreases were found in performing both mental and manual activities as the sound levels increased. On the other hand, at noise levels as low as 40 dB, the negative connotation of external road traffic noise can be responsible for the decline in working performance ( Müller et al, 2023 ). This means that less frequent negative events (e.g., cars or motos pass-by and sirens) combined with natural or anthropic sounds may induce a positive emotional state in the individuals without draining attentive sources.…”
Section: Resultsmentioning
confidence: 99%